Effect of Experimental Operations on the Limiting Current Density of Oxygen Reduction Reaction Evaluated by Rotating‐Disk Electrode. Issue 5 (31st January 2020) - Zhong, Guoyu; Xu, Shurui; Liu, Lei; Zheng, Cheng Zhi; Dou, Jingjing; Wang, Fengye; Fu, Xiaobo; Liao, Wenbo; Wang, Hongjuan
Abstract: The universal linear scan voltammogram measurement on the rotating disk electrode (RDE) has been identified as a simple method to investigate the oxygen reduction activity of electrocatalysts. The steady‐state limiting current density I lim indicates the maximum diffusion current density in the oxygen reduction reaction (ORR) during RDE measurement, which should be a fixed value in theory for a 4e ORR in a particular concentration solution and at a certain rotate speed. However, in experiments, I lim is always variable and smaller than theoretical value even though with the same the catalyst, electrode, and rotator. So the impact of various experimental operating parameters on I lim is highly necessary to be investigated. In this paper, factors, such as catalyst loading, O2 inlet condition, O2 flow rate, gas tightness, solution concentration, and purity, have been investigated for their effects on the I lim of ORR on three typical catalysts (20 % commercial Pt/C, Iron/Nitrogen/Carbon‐catalyst and N‐doped carbon nanotubes). The results indicate that the catalyst loading and O2 inlet condition are the key factors influencing the I lim of ORR. While, the O2 flow rate, gas tightness, solution concentration, and purity have little influence on the I lim of ORR. The correct I lim could be obtained under the optimized catalyst loading and the O2 inlet with an extended sand core tube. Abstract : Current affairs : The effect of catalyst loading, O2 inlet condition, and electrolyte viscosity on the steady‐state limiting current density ( I lim ) for the oxygen reduction reaction (ORR) were investigated, and the results were confirmed by rotating‐disk electrode tests on Pt/C, Fe−N−C, and N−CNT catalyst. The catalyst loading and O2 inlet condition were the critical factors for obtaining correct I lim . However, O2 flow, gas tightness, and solution concentration and purity also have an influence, albeit weak, on the ORR I lim .